Sleep Deprivation as a Risk Factor for Injuries in Athletes - Wojtczak, Karolina; Skupińska, Olga; Antczak, Joanna; Fenrych, Urszula; Lipska, Julia; Hamerska, Laura; Hamerska, Julia; Bocianiak, Bogumił; Ruta, Damian; Kajka, Anna (Quality in Sport, 2024)
Introduction: In recent years, sleep deprivation has increasingly been recognized as a significant factor influencing athletic performance. The basal sleep requirement for healthy adults slightly differs from the sleep needs of individuals who regularly engage in sports. Furthermore, athletes frequently experience sleep loss due to their active and busy schedules. The impact of insufficient sleep on physical and cognitive functions can significantly impair the body's functioning and lead to serious consequences. Purpose of the study: The aim of the study was to emphasize the prevalence of sleep deficiency among athletes, demonstrate how insufficient sleep affects various body functions, and explore its impact on injury risk across different sports disciplines. Materials and methods: A literature review was conducted using PubMed and Google Scholar. Articles were selected based on specific keywords and then assessed for their relevance and suitability for inclusion in this review. Results: The findings indicate that athletes frequently experience sleep problems due to factors such as training schedules, stress, night performances, and travel, with individual sport athletes getting less sleep compared to those in team sports. Sleep deprivation negatively impacts physiological and cognitive functions and is significantly associated with increased injury incidence in sports like soccer, volleyball, and basketball, although results are inconsistent in swimming, cycling, and running, highlighting the need for further research considering factors like training load and individual sleep variability.